Effects of Information Technology–Based Two-Way Referral on Diagnosis and Management of Cervical Lesions: A Cluster-Controlled Trial in China. (July 2018) - Jin, Long-Mei; Xu, Ling; Xu, Jun; Zhang, Xiao-Hua; Zhang, Lin-Lin; Zhu, Li-Hong; Yang, Hui-Bin; Zhang, Lei; Yao, Yan; Feng, Hua
This study investigates the effectiveness of information technology–based 2-way referral in the diagnosis and management of cervical lesions in Minhang District, Shanghai, China. Women who underwent screening for cervical lesions in 4 community health centers constituted the intervention group, whereas women from the other 9 community health centers were included as controls. The diagnosis rate of cervical lesions was higher in the intervention group (7.61%) than in the control group (0.36%; P = .000). The diagnosis rate of early cervical lesion was 97.11% in the intervention group and 85.71% in the control group, showing no statistically significant differences ( P = .080). However, early diagnosis rate of precancerous lesion was much higher in the intervention group (95.45%) compared with the control group (64.29%; P = .001). In conclusion, higher effectiveness of early diagnosis and management of cervical lesions was observed in the intervention group compared with the control group.